Pertussis Syndrome. A Case Report - Alina Esther González Hermida; Miriam Costa Cruz; Eduardo Castañeda Álvarez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Pertussis-like syndrome and whooping cough-like illness are the terms used to refer to the indistinguishable signs and symptoms of whooping cough in the absence of laboratory tests to confirm the presence of the bacteria that causes it. Although there are no reported cases in Cuba, it is important to keep paying attention to the most representative symptoms of this disease, since there has recently been a resurgence of whooping cough in the world. Therefore, it is relevant to present the case of a patient with a two-week history of upper respiratory symptoms and dry cough. These symptoms intensified, so she attended the emergency service of her health area.